(untitled) (JULACE: Journal of the University of Namibia Language Centre, 2018)
As a signifier “African writing” is suitably pluralistic in its potential for denotation and connotation and delimitation of thematic concern. Wearing an ambiguous qualifier such as “African” the contestable positions taken for granted for this cultural tag – which had camouflaged as incontrovertible – are mediated by the pluralism of the nominal which it qualifies. The erstwhile monolith and subject/object of literary/critical discourse fissures viscerally agreeably into fluid ethnic, linguistic and cultural heterogeneity with the result that both the literature and the study based on this literature transform into semantically elastic nondescript items in a state of unremitting variability. Which condition seems compatible with postmodernist insistence of organic connections and disconnections between the system of sound and that of reality according to Saussurean linguistics and Barthesian associative distinction between signifier, signified and sign. Calibrated synchrony deepens the complexity of a subject/concept already detached from signifier, a changing and changeable signified that is stratified and is multilingual multiracial multicultural.